Translational control of vesicular stomatitis virus protein synthesis: isolation of an mRNA-sequestering particle. - Rosen, C A (1982)
An mRNA-ribonucleoprotein particle (mRNP) was found in vesicular stomatitis virus (VSV)-infected Chinese hamster ovary cells. The particle was present 3 and 4.5 h after infection but was barely discernible at 2 h. The mRNP (buoyant density, 1.56 g/cm3), which cosedimented with viral nucleocapsid in a sucrose density gradient at approximately 120 to 160S, was separable from nucleocapsid (buoyant density, 1.31 g/cm3) by CsCl density gradient centrifugation. It contained all five VSV mRNAs and, almost exclusively, viral N protein. Some host mRNA and host protein was also present in the particle. The intact mRNP was incapable of stimulating protein synthesis in an in vitro protein-synthesizing system, although the VSV mRNA isolated from the particle by phenol extraction was functional in vitro. In contrast, intact polysomes stimulated cell-free protein synthesis to the same extent as purified polysomal mRNA. By 4.5 h after infection, 97% of the functional mRNA in vivo was associated with the mRNP, and only 3% was on polysomes. The amount of polysomal mRNA at 4.5 h after infection was only 31% of that found at 2 h after infection; this was reflected by the 76% decrease observed in the rate of in vivo protein synthesis at 4.5 h relative to that found at 2 h. Thus, it appears that the mRNP serves as an organelle which sequesters the large excess of VSV mRNA that is normally made during secondary transcription.